Penggunaan Model Inkuiri Terbimbing Berbantuan Media Audio Visual dalam Meningkatkan Kualitas Pembelajaran IPA pada Peserta Didik Kelas V SDN 111/IX Desa Muhajirin - Halimah Halimah (Universitas Batanghari Jambi, 2020)
This research based from the low quality of science learning in fifth grade students of SDN 111 / IX Muhajirin Village. This is indicated by the discovery of several problems including the teacher is not optimal in guiding students to search and find the concept of learning material independently, so that students have not been motivated and facilitated to independently learn the subject matter with their own pemenuan, teachers are less guiding students in providing problem so that students are not accustomed to thinking critically and analytically, it is supported by low student learning outcomes data with classical completeness reaching 45%. This type of research is a classroom action research conducted in three cycles. Each cycle is carried out in one meeting consisting of planning, implementation, observation and reflection. The subjects of this study were teachers and students of class V SDN 111 / IX Muhajirin Village with a total of 36 students. The results showed the skills of the first cycle teachers received a score of 25 with sufficient criteria, the second cycle obtained a score of 34 with very good criteria and cycle III obtained a score of 36 with very good criteria. Activities of students in the first cycle obtained an average total score of 18.9 with sufficient criteria, second cycle obtained an average total score of 26.4 with good criteria and cycle III obtained an average total score of 30.5 with good criteria. Learning outcomes of students in cycle I obtained an average score of 62.56, cycle II obtained an average score of 71.61 and cycle III obtained an average score of 78.22. The percentage of classical completeness learning outcomes of students in cycle I percentage 56%, cycle II percentage 78% and cycle III percentage 83% . So that it can be concluded that guided inquiry model assisted by audio-visual media can improve the quality of science learning in class V students of SDN 111 / IX Muhajirin Village.